PERAN GURU SEJARAH DALAM MENANAMKAN NILAI-NILAI KEPAHLAWANAN PADA SISWA SMA NEGERI 6 PROVINSI MALUKU UTARA - Zulkifli, Zulkifli; Radjilun, Mus S (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
The aim of this research is to find out the extent of the role of history teachers in imparting heroic values ​​to students at SMA Negeri 6 North Maluku Province, and to provide an understanding of the process of forming the Indonesian nation through a long history to achieve independence. From the results of this research, it is clear that instilling national heroic values ​​can have a positive impact on students because they are motivated to take part in the teaching and learning process in history subjects and can provide awareness for students to know about national heroes in the struggle to maintain the independence of the unitary state of the Republic of Indonesia. Apart from that, by instilling heroic values, it can provide awareness for students because they are part of the generation of the Indonesian nation who have a sense of pride and love for their country which can make the name of this nation proud through the achievements of each student to achieve independence. in the present and the future.